PEMBUATAN DAN UJI ORGANOLEPTIK SEDIAAN GEL DAUN PEGAGAN (Centella asiatica L. Urban) DENGAN DAGING LIDAH BUAYA (Aloe vera) UNTUK LUKA BAKAR - Septiani, Yurika; Puspariki, Jenta; Farhan, Farhan (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2020)
Background: A burn is damage to the skin tissue caused by hot objects, electric shock, chemicals or radiation. Herb Centella asiatica and aloe vera is a plant that is know to have a healing effect on burns. Objective: This study aims to make burn gel preparations made from aloe vera with pegagan and to determine the stability seen from the organoleptic test for 3 weeks. Method: The research method used is action research which consists of four components, namely planning, acting, observing and reflecting. Preparations were made into 3 formulations of gotu kola leaf simplicia and aloe vera gel with the composition of F1 (75% gotu kola leaves, 25% aloe vera), F2 (50% gotu kola leaves, 50% aloe vera), F3 (25% gotu kola leaves, 75 % Aloe vera). Results: The combination gel preparation of Aloe Vera Meat with Gotu Kola made in this study is in 3 (three) formulations, namely F1, F2 and F3 with the composition F1 (75% Gotu kola Leaf Extract, 25% Aloe Vera Meat Extract) produces a semi-solid form, dark brown green, the distinctive aroma of gotu kola extract with a soft, sticky texture. For F2 with the composition (50% gotu kola extract and 50%, aloe vera meat extract), it produces a semi-solid form, dark brown green, with a distinctive aroma of gotu kola extract with a sticky slippery texture. F3 with the composition (25% gotu kola extract, 75% aloe vera meat extract) produces a semi-solid form, dark brown green, with a distinctive aroma of gotu kola extract with a sticky liquid texture. Conclusion: The conclusion of this study is that the gel for F1 burns is stable in room temperature storage and safe for use by the community with a pH range of 6.